A Passive Fault Tolerance Strategy for Super-Twisting Algorithm-Based Sliding Mode Control With Barrier Function for Quadrotor UAVs - Yujuan Wang; Congmin Ji (IEEE Access)
Unknown external disturbances and actuator failures significantly affect the performance and flight safety of quadrotor unmanned aerial vehicles (UAVs) during task execution. To address this challenge, this paper proposes a barrier function-based passive fault-tolerant control strategy combining a super-twisting algorithm (STA) with sliding mode control (SMC). Firstly, STA based on potential barrier function is used to compensate unknown fault coefficients and external disturbances. This strategy does not need parameters related to actuator faults and external disturbances, and relies on its sign function-based controller design and robustness to overcome the adverse effects of unknown parameters. Furthermore, considering the transient response of the system, combined with the SMC strategy, the system has a faster response speed. In addition, the finite-time stability of the closed-loop system is guaranteed by Lyapunov theory. Finally, two sets of simulation experiments verify the effectiveness and superiority of the proposed control method.